2011
DOI: 10.1093/rfs/hhr027
|View full text |Cite
|
Sign up to set email alerts
|

Margin-based Asset Pricing and Deviations from the Law of One Price

Abstract: In a model with heterogeneous-risk-aversion agents facing margin constraints, we show how securities' required returns increase in both their betas and their margin requirements. Negative shocks to fundamentals make margin constraints bind, lowering risk-free rates and raising Sharpe ratios of risky securities, especially for high-margin securities. Such a funding-liquidity crisis gives rise to "bases," that is, price gaps between securities with identical cash-flows but different margins. In the time series, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
411
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 591 publications
(440 citation statements)
references
References 57 publications
23
411
6
Order By: Relevance
“…In other words, deterioration in market liquidity tightens traders' margin constraints and thus funding liquidity, which in turn further reduces market liquidity. Garleanu and Pedersen (2011) developed a dynamic equilibrium model to show that margin constraints can lead to deviations from the law of one price.…”
Section: Credit Cyclesmentioning
confidence: 99%
“…In other words, deterioration in market liquidity tightens traders' margin constraints and thus funding liquidity, which in turn further reduces market liquidity. Garleanu and Pedersen (2011) developed a dynamic equilibrium model to show that margin constraints can lead to deviations from the law of one price.…”
Section: Credit Cyclesmentioning
confidence: 99%
“…Studies relating margin requirements and the shadow cost of funding to asset prices (hence, the presence of TED Spread risk) in a credit constrained environment are found in Luttmer (1996), Bernardo and Welch (2003) and more recently in Brunnermeier and Pedersen (2009), Ashcraft et al (2010) and Gârleanu and Pedersen (2011). Those articles assume that agents are heterogeneous in a sense that they differ in their relative risk aversion and may face different margin constraints for taking leverage positions.…”
Section: Related Literaturementioning
confidence: 99%
“…During times of crisis, as capital is constrained, expected returns are positively related to margins because agents face additional costs of funding. Credit constraints can also cause adverse impacts on asset prices, and the worst of all, according to Gârleanu and Pedersen (2011) is the failure of the "Law of One Price" (LoOP), by which two different assets with similar cash flows are negotiated under different prices, as margin requirements may differ. Also, Hedegaard (2011) studied margin impacts on commodity future returns, and found that an increase in futures margins, in which speculators hold long positions, reduces the futures price of long-term contracts.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations